Erythropoietin Does Not Enhance Skeletal Muscle Protein Synthesis Following Exercise in Young and Older Adults - Lamon, Séverine; Zacharewicz, Evelyn; Arentson-Lantz, Emily; Gatta, Paul A. Della; Ghobrial, Lobna; Gerlinger-Romero, Frederico; Garnham, Andrew; Paddon-Jones, Douglas; Russell, Aaron P. (Frontiers in Physiology, 2016)
Purpose: Erythropoietin (EPO) is a renal cytokine that is primarily involved in hematopoiesis while also playing a role in non-hematopoietic tissues expressing the EPO-receptor (EPOR). The EPOR is present in human skeletal muscle. In mouse skeletal muscle, EPO stimulation can activate the AKT serine/threonine kinase 1 (AKT) signalling pathway, the main positive regulator of muscle protein synthesis. We hypothesized that a single intravenous EPO injection combined with acute resistance exercise, would have a synergistic effect on skeletal muscle protein synthesis via activation of the AKT pathway. Methods: Ten young (24.2 ± 0.9 y) and 10 older (66.6 ± 1.1 y) healthy subjects received a primed, constant infusion of [ring-13C6] L-phenylalanine and a single injection of 10,000 IU epoetin-beta or placebo in a double-blind randomized, cross-over design. Two hours after the injection, the subjects completed an acute bout of leg extension resistance exercise to stimulate skeletal muscle protein synthesis. Results: Significant interaction effects in the phosphorylation levels of the members of the AKT signaling pathway indicated a differential activation of protein synthesis signalling in older subjects when compared to young subjects. However, EPO offered no synergistic effect on vastus lateralis mixed muscle protein synthesis rate in young or older subjects. Conclusions: Despite its ability to activate the AKT pathway in skeletal muscle, an acute EPO injection had no additive or synergistic effect on the exercise-induced activation of muscle protein synthesis or muscle protein synthesis signalling pathways.